The complete mitochondrial genome of yellowfin seabream, Acanthopagrus latus (Percoiformes, Sparidae) from Beibu Bay. Issue 4 (3rd April 2021) - Pan, Chuanyan; Gao, Chongmin; Chen, Tao; Chen, Xiuli; Yang, Chunling; Zeng, Digang; Feng, Pengfei; Jiang, Weiming; Peng, Min
Abstract: The yellowfin seabream, Acanthopagrus latus Houttuyn 1782, is a commercially and ecologically important species and a good model for studies of sexual differentiation. In this study, the complete mitochondrial genome of A. latus has been determined, which is 16, 635 base pairs (54.3% A + T content) in length and consists of 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and a 948 bp D-loop region. The phylogenetic analyses showed that A. latus has a close relationship with Acanthopagrus schlegelii Bleeker 1854.